Validation of a Modified QuEChERS Method for the Determination of Selected Organochlorine Compounds in Honey - Radosław Lewiński; Agnieszka Hernik; Monika Liszewska; Brian Buckley; Katarzyna Czaja; Wojciech Korcz; Anna Słomczyńska; Paweł Struciński (Molecules, 2023)
Honey is considered to be a health-promoting food product. Therefore, it is assumed that it should be free of contaminants. Although the use of organochlorine pesticides (OCPs) was banned a few decades ago in developed countries, persistent organic pollutants (POPs) are still detected in various environmental and biological matrices, including food. These contaminants exhibit toxic properties and bioaccumulate in some food chains. The validation of a modified QuEChERS extraction method was successfully performed for o,p’-DDT, o,p’-DDE, o,p’-DDD, p,p’-DDT, p,p’-DDE, p,p’-DDD, heptachlor and dieldrin. 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB 153) was used as an internal standard. The modification involved changing the solvent from acetonitrile to n-hexane after extraction. Quantitation was carried out using gas chromatography with an electron capture detector (µECD). The mean recovery values for o,p’-DDT, o,p’-DDE, o,p’-DDD, p,p’-DDT, p,p’-DDE, p,p’-DDD and dieldrin, spiked at 2.9 ng/g and 20 ng/g, ranged from 64.7% to 129.3%, and, for heptachlor spiked at 5.6 ng/g and 20 ng/g, ranged from 68.0% to 88.3%. The relative standard deviation (RSD) for these concentrations did not exceed 20%, and the within-laboratory reproducibility was below 20%, except o,p’-DDE and p,p’-DDT, which were 25.2% and 20.7%, respectively. This modified QuEChERS extraction method for selected organochlorine compounds was demonstrated as effective for routine testing in honey.